Exciton Modulation in Perylene-Based Molecular Crystals Upon Formation of a Metal-Organic Interface From Many-Body Perturbation Theory - Shunak, Liran; Adeniran, Olugbenga; Voscoboynik, Guy; Liu, Zhen-Fei; Refaely-Abramson, Sivan (Frontiers in Chemistry, 2021)
Excited-state processes at organic-inorganic interfaces consisting of molecular crystals are essential in energy conversion applications. While advances in experimental methods allow direct observation and detection of exciton transfer across such junctions, a detailed understanding of the underlying excitonic properties due to crystal packing and interface structure is still largely lacking. In this work, we use many-body perturbation theory to study structure-property relations of excitons in molecular crystals upon adsorption on a gold surface. We explore the case of the experimentally-studied octyl perylene diimide (C8-PDI) as a prototypical system, and use the GW and Bethe-Salpeter equation (BSE) approach to quantify the change in quasiparticle and exciton properties due to intermolecular and substrate screening. Our findings provide a close inspection of both local and environmental structural effects dominating the excitation energies and the exciton binding and nature, as well as their modulation upon the metal-organic interface composition.